Estimating Poverty in Kinshasa by Dealing with Sampling and Comparability Issues - Batana, Yele Maweki; Masaki, Takaaki; Nakamura, Shohei; Viboudoulou Vilpoux, Mervy Ever (World Bank, Washington, DC, 2021)
This paper proposes monetary poverty and inequality estimates for Kinshasa using a new Kinshasa household survey implemented in 2018. Given the obsolescence of the sampling frame, the survey was sampled using satellite imagery. However, the collection of data in the field was affected by sampling errors that are likely to compromise the representativeness of the sample. After addressing these sampling issues and dealing with some comparability issues with the 2012 survey, the paper shows that poverty and inequality increased significantly during 2012–18 in Kinshasa. Poverty has increased in the city by 12 percentage points, from 53 to 65 percent, partly due to the loss of purchasing power following the sharp depreciation in 2017. Other explanatory factors include demographic factors, human capital, and spatial factors. The deterioration in well-being also appears to have been exacerbated by the onset of the COVID-19 pandemic through decline in labor and nonlabor income and disruptions in goods and services markets and public services.